Optoelectronics an introduction to materials and devices - Singh, Jasprit (McGraw-Hill series in electrical and computer engineering., 1996)
Aimed at graduate students in electrical engineering, this text provides a broad understanding of the rapidly growing field of optoelectronics. An integrated approach is used, covering topics in: applied optics; physics of optical response; and semiconductor optoelectronic devices.